CARYA BAKSYA SEBAGAI SARANA ANAK DESA UNTUK MENGASAH KREATIVITAS DALAM MEWUJUDKAN DESA MAJU MELALUI PELESTARIAN BUDAYA - Pramusinta, Yulia; Agustin, Fanisa Arin; Af'idah, Nuris Watul; Rosidah, Emil Lailatur; Mahsunah, Tsaniyatul; Wahyuddin, M. (As-Sidanah, 2025)
Culture in Kepudibener Village, Turi Sub-district, Lamongan Regency, is experiencing cultural decline due to the rampant use of gadgets in early childhood. In overcoming the fading of culture in Kepudibener Village, cultural preservation efforts are needed that can foster a sense of love and high curiosity about all aspects of culture. The purpose of this research is to develop the creativity of village children through the concept of love for local culture. The research subjects were Kepudibener villagers. The research method used a descriptive qualitative method. The data collection instrument used interview, observation, and documentation techniques. From the research, it was found that the creativity of the Kepudibener village community can increase well. This can be proven by the Carya baksya program, namely the cultural lenggak program, scent craft, and ecoprint, which can increase the creativity of villagers. Carya baksya is a program that has been arranged to preserve the local culture of the people in Kepudibener village.